1988
DOI: 10.1111/j.1365-2125.1988.tb03291.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbidopa and indomethacin on the renal response to gamma‐ L‐glutamyl‐L‐dopa in normal man.

Abstract: 1 The renal response to y-L-glutamyl-L-dopa (gludopa, 25 ,ug kg-1 min-') was investigated in seven normal male volunteers. The effects of oral carbidopa (100 mg) and indomethacin (100 mg) on the response to gludopa were studied in the same group. 2 Gludopa at this dose level produced a 900-fold increase in urine dopamine excretion and caused a natriuresis and suppression of plasma renin activity with only minor effects on pulse rate and blood pressure. 3 Carbidopa inhibited the increase in dopamine excretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The increased blood pressure is associated with increased renal renin activity. Dopamine and dopaminergic drugs have been reported to increase renin secretion in some studies and to decrease it in other studies (8,(11)(12)(13). These apparently conflicting reports can now be explained by the contrasting effects on renin secretion after stimulation of dopamine receptor subtypes.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The increased blood pressure is associated with increased renal renin activity. Dopamine and dopaminergic drugs have been reported to increase renin secretion in some studies and to decrease it in other studies (8,(11)(12)(13). These apparently conflicting reports can now be explained by the contrasting effects on renin secretion after stimulation of dopamine receptor subtypes.…”
Section: Discussionmentioning
confidence: 80%
“…The other D 1 -like receptor, the D 1B receptor, is not expressed in rat juxtaglomerular cells (8). D 2 -like receptors probably mediate the inhibitory effect of dopamine on renin secretion (11)(12)(13). Since D 3 but not D 2 receptors are present in rat juxtaglomerular cells and since D 3 receptor stimulation inhibits cAMP accumulation in these cells, we have suggested that the D 3 receptor may be responsible for the dopamine-mediated decrease in renin secretion in these cells (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that effects of gludopa are abolished by prior treatment with carbidopa (Jeffrey et al, 1988) which prevents conversion of gludopa to dopamine. Glutyrosine, which is structurally similar to gludopa does not increase urine dopamine and is not natriuretic providing evidence against a non specific effect of gludopa.…”
Section: Discussionmentioning
confidence: 99%
“…If urinary DA is formed from the uptake of circulating DOPA and is decarboxylated in the kidney, then inhibition of L-AAAD should decrease urinary DA excretion, as has actually been reported. [40][41][42] DA is known to suppress Na + , K + -ATPase activity in the proximal convoluted tubule (PCT) and the thick ascending limb of the loop of Henle. 43 The Na + , K + -ATPase is located mainly on the basolateral membranes, where the stimulatory effect of DA on phospholipase C predominates, resulting in activation of protein kinase C and inhibition of Na + , K + -ATPase activity.…”
Section: (⌬) Mbp Dbp U-f-da U-t-da U-kal U-f-na U-t-na U-na P-f-da P-mentioning
confidence: 99%